Sustainable and nonconventional construction materials using inorganic bonded fiber composites - Savastano Junior, Holmer; Fiorelli, Juliano; Santos, Sergio Francisco dos (Woodhead Publishing series in civil and structural engineering., 2017)
Sustainable and Nonconventional Construction Materials Using Inorganic Bonded Fiber Composites presents a concise overview of non-conventional construction materials with a strong focus on alternative inorganic bonded fiber composites and their applications as construction components. It outlines the processing and characterization of non-conventional cementitious composites, which will be of great benefit to both academic and industrial professionals interested in research, development, and innovation on inorganic bonded fiber composites. The book gives a comprehensive review of the innovative research associated with building components based on inorganic bonded composites. Exploring both natural fibers as reinforcing elements and alternative inorganic binders based on agricultural and industrial wastes, this book also considers the performance and applications of fibrous composites as construction materials and components. Dedicated to analyzing recent developments in inorganic fiber composites researchDiscusses the broader subjects of processing, characterization, performance, and applications of non-conventional construction materials.